2018
DOI: 10.1111/exd.13488
|View full text |Cite
|
Sign up to set email alerts
|

A novel lateral flow immunoassay for the rapid detection of anti‐Dsg3 IgG serum autoantibodies in pemphigus vulgaris

Abstract: Pemphigus vulgaris (PV) is a severe autoimmune blistering disease of the skin and mucous membranes. As autoantibodies play an essential role in the disease pathogenesis, the serological detection of anti-desmoglein 3 IgG represents a central tool in the diagnosis of the disease. In this study, we show the validation of a novel lateral flow immunoassay (LFIA) which rapidly detects anti-desmoglein 3 (Dsg3) IgG in human serum. In contrast to other diagnostic procedures, the assay is compact and simple to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Recently, a novel lateral flow immunoassay (LFIA) was developed (82). It detects anti-Dsg 3 IgG in human sera.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a novel lateral flow immunoassay (LFIA) was developed (82). It detects anti-Dsg 3 IgG in human sera.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other diagnostic procedures, the assay is simpler and faster. LFIA was validated on a collection of 200 sera and showed a sensitivity and specificity of 78.1 and 97.1%, respectively (82).…”
Section: Introductionmentioning
confidence: 99%
“…Pemphigus vulgaris (PV) is a severe tissue‐specific autoimmune bullous disease that causes blistering of the skin and mucous membranes. IgG autoantibodies that bind predominantly to the cadherin‐type adhesion molecule desmoglein (Dsg)3 have been implicated in PV 1,2 . These autoantibodies, although produced by B cells, are under the regulatory control of several lineages of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…IgG autoantibodies that bind predominantly to the cadherin-type adhesion molecule desmoglein (Dsg)3 have been implicated in PV. 1,2 These autoantibodies, although produced by B cells, are under the regulatory control of several lineages of T cells. Studies have shown that T cells play an important role in the regulation of B-cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…Pemphigus is a life‐threatening autoimmune disease characterized by mucocutaneous blister formation which is mainly mediated by IgG autoantibodies formed against the desmosomal adhesion proteins, desmoglein 3 (Dsg3) and/or Dsg 1 . Nowadays, other pathogenic mechanisms such as apoptolysis, elevated proinflammatory cytokines and aberrant cell signalling pathways (p38MAPK‐signaling pathway) have been suggested in this regard .…”
Section: Introductionmentioning
confidence: 99%